Animal stories - Blyton, Enid (London: Hodder Children's Books, 2019)
A fantastic collection of 30 stories about animals. From pet puppies to woodland wildlife, garden birds to pond-dwelling frogs, Enid Blyton was a devoted and knowledgeable animal-lover.
Keywords: Children's stories; Fiction